Employment trends and economic factors in MENA region: An ARDL approach - Abid, Ihsen (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the relationship between macroeconomic variables and employment in the MENA region, focusing on the dynamics of economic growth, trade openness, investment, and services sector development. The aim is to provide insights into both the short- and long-term factors affecting labor force participation rates in the region. The research employs the Autoregressive Distributed Lag (ARDL) model to analyze time-series data, capturing the interplay between key macroeconomic variables. The model is chosen for its flexibility in handling variables of different integration orders. The results reveal significant relationships between the explanatory variables and employment in the MENA region. Economic growth, investment, and trade openness exhibit varying impacts in the short and long run, while the services sector emerges as a critical driver of employment. The bounds test confirms the existence of a long-run relationship, and the error correction model indicates strong adjustments towards equilibrium. This research contributes to the existing literature by employing the ARDL approach to explore employment dynamics in the MENA region, providing both theoretical and empirical insights. The findings offer valuable policy recommendations for enhancing employment outcomes in the region through targeted macroeconomic strategies.